Clinical delineation and immunopathogenesis of autoimmune encephalitis - Varley, J (2019)
Neuroglial surface antibody (NSAb)-mediated diseases are autoimmune brain diseases including autoimmune encephalitis (AE). Early immunotherapy improves outcome making prompt diagnosis crucial. In N-methyl D-aspartate receptor antibody encephalitis (NMDAR-AbE), improved description of the associated movement disorder (MD) should aid early recognition. Similarly, clarifying the purported association between NMDAR-antibodies and systemic lupus erythematosus (SLE) would help clinicians. Finally, the underlying immunology in patients with AE secondary to leucinerich glioma inactivated protein-1 (LGI1) and contactin-associated protein-like 2 (CASPR2) antibodies remains unexplored and a likely source of novel, targeted immunotherapies.